Hepatitis C virus infection and risk of osteoporotic fracture: A systematic review and meta-analysis - Karn Wijarnpreecha (2018)
© 2018 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd Background/objectives: Hepatitis C virus (HCV) infection is one of the most common causes of chronic liver disease. Several epidemiologic studies have suggested that patients with HCV infection might have a higher risk of osteoporotic fracture. However, the data are inconclusive. This systematic review and meta-analysis was conducted with the aims to summarize all available evidence. Methods: A literature search was performed using MEDLINE and EMBASE database from inception to June 2016. Studies that reported relative risks, odd ratios, or hazard ratios comparing the risk of osteoporotic fracture among HCV-infected patients versus subjects without HCV infection were included. Pooled risk ratio (RR) and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method. Results: Three studies with 362,285 participants met our eligibility criteria and were included in analysis. We found a significantly higher risk of osteoporotic fracture among patients with HCV infection with RR of 1.53 (95% CI 1.09 to 2.14). Conclusions: Our study demonstrated an increased risk of osteoporotic fracture among HCV-infected patients. Further studies are required to clarify how this risk should be addressed in clinical practice.